BRITISH AND AMERICAN ACCENTS ANALYSIS OF THE CONTESTANTS OF THE PUBLIC SPEAKING ACADEMY COMPETITION IN 2017: SOCIOLINGUISTIC PERSPECTIVE - Riyanti Sri Astuti; Ayang Winda Sri Widianingsih; Nurfithri (Jurnal Sastra - Studi Ilmiah Sastra, 2024)
The research entitled British And American Accents Analysis Of The Contestants Of The Public Speaking Academy Competition In 2017. This research aims to analyze the pronunciation of the British accent and the pronunciation of the American English accent. Using qualitative descriptive methodology, this study collected and analyzed speech data from two YouTube videos. This analysis focuses on identifying the distinct phonological features that characterize British and American accents. The findings show differences in pronunciation between British and American accents. The British accent displays strikingly non-rhotic features, as seen in the omission of the letter 'r' at the end of words, in contrast to the rhotic nature of the American accent which emphasizes the clear pronunciation of the consonant 'r'. Additionally, British accents often use long vowels, while American accents tend to favor short vowels with greater clarity. Additionally, American accents often exhibit diphthongization or reduction of unrounded vowels, which contributes to the complexity of phonological variation. This study emphasises the importance of recognising the phonological differences between British and American accents, especially in the context of public speaking competitions. The observed discrepancies reflect the many language landscapes influenced by historical, geographical, and cultural influences. This study advances our understanding of linguistic variety and accent variance within English-speaking populations by throwing light on these distinctions. Further research should look into the effects of accent differences on communication and perception in multicultural and global environments.Keywords: sociolinguistics, accents, british, english american, phonological